Physiological Ecology of Tropical Plants - Lüttge, Ulrich (Springer, 2017)
Introduction -- Large-Scale Sensing and Diagnosis in Relationto the Tropical Environment -- Tropical Forests. I. Physiognomy and Functional Structure -- ropical Forests. II. Ecophysiological Responses to Light...